Sensory and Motor Deficits in the Elderly: - Elisa M. Chavez, DDS; Jonathan A. Ship, DMD (Blackwell Synergy, 2000)
Hearing, vision, orthopedic, and speech disorders are the most common impairments in the elderly. Older adults experience other sensory impairments such as olfactory and gustatory dysfunction, as well as oral motor problems including difficulty with mastication, speech, and swallowing. These disorders can directly affect oral health and can impair dental treatment. Therefore, it is imperative that dental health practitioners be cognizant of these conditions and aware of the impact these conditions and their treatments can have on oral health and function. Dental professionals may need to use different communication techniques for patients with vision or hearing losses.